O processo de construção identitária e pertencimento étnico-racial de estudantes pardos no ensino superior - Almeida, Tatiane Martins Moacir de (2022)
The present work aimed to analyze the processes of identity construction and ethnicracial belonging of brown students, coming from interracial families and students of higher education at the Federal University of São Carlos. Mostly, studies on affirmative action policies and processes of democratization of access to higher education in Brazil have prioritized the analysis of the profile of students in the economic, gender, ethnic-racial and area of entry dimensions, in addition to studies on performance, trajectory and insertion in the labor market. In this sense, this research is configured as a case study that was developed through bibliographic analysis, through interviews with self-declared brown students from interracial families, from different areas of knowledge, whether or not they opted for admission through the affirmative. The interviews made it possible to listen to self-declared brown students who experience the dilemma of belonging or not belonging due to their skin pigmentation and phenotypic traits. The speeches demonstrate that the university impacts on the construction of identity and ethnic-racial belonging, in the same way it has an impact on families when dealing with issues related to race and gender and by encouraging other family members to enter a public university.